New Observations on Bone Quality in Mild Primary Hyperparathyroidism as Determined by Quantitative Backscattered Electron Imaging - Roschger, Paul; Dempster, David W; Zhou, Hua; Paschalis, Eleftherios P; Silverberg, Shonni J; Shane, Elisabeth; Bilezikian, John P; Klaushofer, Klaus (Journal of bone and mineral research, 2007)
Bone mineralization density distribution, an important aspect of bone material quality, was determined in mild primary hyperparathyroidism using quantitative backscattered electron imaging. A strong correlation between bone turnover status and degree and heterogeneity of mineralization was found. Further studies are needed before we can draw conclusions about fracture risk in this disorder. Introduction: Mild primary hyperparathyroidism (PHPT) is best characterized by asymptomatic hypercalcemia, most commonly in the absence of classical signs and symptoms. Hence, there is need to characterize this disorder with particular attention to the skeleton. Materials and Methods: We analyzed bone mineralization density distribution (BMDD) in iliac crest bone biopsies from patients with PHPT in 51 subjects (16 men, 28–68 years of age; 35 women, 26–74 years of age) by quantitative backscattered electron imaging (qBEI). The BMDD variables quantified are as follows: CaMEAN, the weighted mean calcium concentration; CaPEAK, the most frequent Ca concentration; CaWIDTH, the width of the distribution, a measure of the mineralization homogeneity; CaLOW, the percentage of bone area that is mineralized below the fifth percentile in the reference range. The results were compared with a reference range that we have previously established. Results: The greatest differences were found in CaWIDTH (+15.7%, p < 0.0001) and CaLOW (+44.7%, p < 0001), both of which were significantly higher in PHPT than control. CaMEAN was significantly lower (−2.5%, p < 0.0001) in PHPT compared with controls. These differences were reversed in seven patients who underwent parathyroidectomy. CaMEAN and CaPEAK variables were negatively, whereas CaWIDTH and CaLOW were positively, correlated with dynamic variables of bone formation: mineralizing surface and bone formation rate as determined by histomorphometry. (r = ±0.3–0.8; p = 0.05–0.0001). These results, which represent the first BMDD measurements in mild PHPT using qBEI, show a reduction in the average mineralization density and an increase in the heterogeneity of the degree of mineralization. These changes correlate significantly with the bone turnover rate. Conclusions: The results are consistent with our previous observations of increased bone turnover in this disease, and consequently, reduced mean age of bone tissue. Reduced mineralization density in patients with PHPT would be expected to reduce the stiffness of bone tissue. These observations are relevant to considerations of fracture risk in PHPT.